Interstitial deletion in Xp22.3 is associated with X linked ichthyosis, mental retardation, and epilepsy - Gohlke, Bernd; Haug, Karsten Georg; Fukami, Maki; Friedl, Waltraut; Noeker, Meinolf; Rappold, Gudrun; Haverkamp, Fritz (Journal of medical genetics, 2000)
We describe monozygotic male twins with an interstitial deletion of Xp22.3 including the steroid sulphatase gene (STS). The twins had X linked ichthyosis, X linked mental retardation, and epilepsy. A locus for X linked mental retardation has been assigned to a region betweenSTS and DXS31 spanning approximately 3 Mb. Recently the locus was further refined to an approximately 1 Mb region between DXS1060 and GS1. By PCR analysis of flanking STS gene markers in our patients we succeeded in narrowing down the locus to between DXS6837 andGS1.
Gesehen am 24.03.2021